Unique Characteristics of the Dorsal Root Ganglion as a Target for Neuromodulation. (1st June 2019) - Esposito, Michael F; Malayil, Rudy; Hanes, Michael; Deer, Timothy
Abstract: Objective: The dorsal root ganglion (DRG) is a novel target for neuromodulation, and DRG stimulation is proving to be a viable option in the treatment of chronic intractable neuropathic pain. Although the overall principle of conventional spinal cord stimulation (SCS) and DRG stimulation—in which an electric field is applied to a neural target with the intent of affecting neural pathways to decrease pain perception—is similar, there are significant differences in the anatomy and physiology of the DRG that make it an ideal target for neuromodulation and may account for the superior outcomes observed in the treatment of certain chronic neuropathic pain states. This review highlights the anatomy of the DRG, its function in maintaining homeostasis and its role in neuropathic pain, and the unique value of DRG as a target in neuromodulation for pain. Methods: A narrative literature review was performed. Results: Overall, the DRG is a critical structure in sensory transduction and modulation, including pain transmission and the maintenance of persistent neuropathic pain states. Unique characteristics including selective somatic organization, specialized membrane characteristics, and accessible and consistent location make the DRG an ideal target for neuromodulation. Because DRG stimulation directly recruits the somata of primary sensory neurons and harnesses the filtering capacity of the pseudounipolar neural architecture, it is differentiated from SCS, peripheral nerve stimulation, and other neuromodulation options. Conclusions: There are several advantages to targeting the DRG, including lower energy usage, more focused and posture-independent stimulation, reduced paresthesia, and improved clinical outcomes.